Stevens-Johnson syndrome/toxic epidermic necrolysis treated with breast milk - Dávalos-Loo, Long Fu Seng (2019)
We report the case of a 3 year-old girl with a Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN), SJS/NET overlap, who was treated with mature breast milk dressings. She had a favorable evolution; the re-epithelialization under the necrotic epidermis initiated on the fourth day of treatment, and completed on the tenth day.